On New Generalizations of Nano-Open Sets in Nano Topological Spaces - Shareef, Hardi A.; Saeed, Parween M. (Majallat Jāmiʻat Bābil, 2025)
This paper focuses on a novel class of. Nano -open sets are known as Nano -open sets, which are related to Nano closed sets in Nano topological spaces. In this paper, we find all forms of the family of Nano -open sets in terms of upper and lower. Approximations of sets and we can easily find Nano -open sets and they are a gate to more study. We also examine the fundamental properties of Nano -open sets and  their relationships with other known classes of Nano.و-open sets in*Nano topological spaces, and introduce related  operators such as the Nano -limit point and Nano -boundary point and investigate the properties of the operators. We aim to refine the understanding of Nano topological spaces and their potential applications.